The Effect of Motivation and Work Environment on Employee Job Satisfaction (Case Study at PT. Latexindo) - Nuraini Kemala Sari; Wilchan; Delta Lumban Gaol (Yayasan Multidimensi Kreatif, 2024)
Employee job satisfaction is an important factor in achieving productivity and good performance in an organization. This study analyzes the understanding of the factors that affect employee job satisfaction can help companies in improving employee performance and retention. This research uses a case study approach involving employees at PT. Latexindo as a research sample. Data was collected through questionnaires given to employee respondents. The variables studied include motivation, work environment, and job satisfaction. Motivation is measured by the level of needs met and the drive to achieve goals. Work environment is measured by factors such as co-worker support, leadership, and physical condition of the workplace. Job satisfaction is measured based on employees' perceptions of their jobs, including salary, recognition, and career development opportunities. The results of this study are expected to provide a better understanding of the factors that affect employee job satisfaction at PT. Latexindo, so that companies can take appropriate steps to improve job satisfaction and employee performance. The data analysis technique used is the Quantitative method using the help of SPSS version 29. This study used Multiple Linear Regression. Primary data collection using questionnaires. Research shows that motivation partially has a positive and significant effect on job satisfaction at PT. Latexindo where tcount 2.990 > ttable 1.687 and significance 0.005 < 0.05. The work environment partially has a positive and significant effect on job satisfaction at PT. Latexindo where tcount 0.877 > ttable 1.687 and significance 0.386 < 0.05. Motivation and Work Environment simultaneously affect and significantly affect job satisfaction at PT. Latexindo Toba Perkasa where Fcalculate is 5.399 while F table is 3.25 and significant 0.05. The results of the research make an important contribution in the field of human resource management. The research can also provide valuable input for other companies in their efforts to improve employee satisfaction and performance.